Karl Polanyi A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (18861964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. In this first full biography of the intellectual's life and work, we learn how personal and historical events structured Polanyi's clear-eyed analyses and complex convictions. He began his career as a bourgeois radical but transitioned into a Christian socialist with ambivalent views on social democracy, communism, the New Deal, and the intellectual provocations of postwar America. The narrative begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The book revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's network of scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Offering a unique portal into an epoch's ruptures, tensions, and upheavals, this biography reflects and condenses extraordinary times through the life of one of its most engaged witnesses